"Prison Bars Will Not Silence the Truth": In El Salvador, the movement of families of people deprived of their liberty is sustaining a struggle for a community stripped of its humanity and reimagining justice in the process. - Grimaldi, Grazzia; López, Yanci (NACLA Report on the Americas, 2025)
The article focuses on the struggles faced by families of people deprived of liberty (PDL) in El Salvador, particularly in the context of the punitive measures and communication restrictions imposed by the government since 2019. Following a state of emergency declared by President Nayib Bukele, families, predominantly women, have organized to denounce the isolation and abuses within the prison system, advocating for their rights and the rights of their incarcerated loved ones. They have developed community networks to share information and support each other, while also navigating the financial burdens associated with sustaining their relatives in prison. The article highlights the critical role these families play in challenging systemic injustices and reimagining concepts of justice amidst a backdrop of increasing state repression and human rights violations.